The relationship between cash holdings, investment opportunities and financial constraint with audit fees - Mohammad Mohammadi; Behzad Kardan; Mahdi Salehi (Emerald Publishing Limited, 2018)
The purpose of this paper is to investigate the relationship between cash holdings, investment opportunities and financial constraint with audit fees in Iran.In order to collect data, all manufacturing companies listed on the Tehran Stock Exchange are used to test the hypotheses during 2008–2015. Panel data and combined data regression model were used for data analysis. Tests were performed using R statistical software.The results obtained from the statistical analysis of research hypotheses indicated that there is a significant relationship between cash holdings and audit fees. Furthermore, the relationship between cash holdings, financial constraints and audit fees was significant. In addition, there was no significant relationship between cash holdings, investment opportunities and audit fees.The current study employed a unique topic in terms of a developing country, and the results may give strength to other developing nations.